FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA PERDARAHAN POST PARTUM PADA IBU BERSALIN DI RSKDIA SITTI FATIMAH MAKASSAR - Rusli Taher; yudiarsi eppang (Stikes Graha Edukasi Makassar, 2020)
Objective: The purpose of this study was to determine the relationship between age, anemia, and parity with the incidence of post partum hemorrhage in maternity mothers. The study was conducted in October 2018 at the District Hospital. Makassar Wedge Labuang. Method: This type of research is an observational method with a cross sectional study approach. The population in this study were all women who experienced post partum hemorrhage in Makassar Sitti Fatimah Hospital as many as 81 people obtained a sample of 62 people with a sampling technique of purposive sampling. Results: The results showed that there was a relationship between age and the incidence of post partum hemorrhage with a value of p = 0,000. The results showed that there was a relationship between anemia and the incidence of post partum hemorrhage with a value of p = 0,000. The results showed that there was a relationship between parity and the incidence of post partum hemorrhage with a value of p = 0,000. Conclusion: The conclusions in this study are age, anemia, and parity have an association with the occurrence of post partum hemorrhage. As a suggestion, especially mothers who have parity 1 if they have plans to get pregnant again. Suggestion: It is expected to pay more attention to her pregnancy by always checking regularly and for mothers who have a parity of more than 3 so they no longer have the desire to add more offspring, this is intended to reduce the risk of subsequent post partum hemorrhage